TOKSISITAS ASETAMINOFEN PADA KHAMIR Candida tropicalis - Heddy Julistiono (The East Java Biological Society, 2011)
Use of the yeast for cell based method to do a screening substances having anti-oxidant property is considered to be simpler and cheaper. In order to develop yeast Candida tropicalis as a tool for evaluation of anti- or pro-oxidant property of substances in cell level, toxicity of an analgesic drug acetaminophen in the yeast had been preliminary studied. Incubation of yeast cell suspension in presence of 0.3% acetaminophen for 2 hours significantly decreased cell viability. Malon dialdehyde, a biochemical marker for cell oxidative damage, increased. Acetaminophen of 0.1% or 0.039% decreased when added in cell yeast suspension or supernatant respectively for 1 hour indicating drug metabolism by cellular and extracellular enzymes. The data indicated that toxicity of the drug in the yeast could be compared to that in mammalian cell where the drug was metabolized by cytochrome P-450 or peroxidase and followed with oxidative stress in cells caused by metabolite byproduct. Toxicity of the drug in the yeast may be in relation with formation of reactive oxygen species. These preliminary data used the yeast for screening antioxidant property of substances against acetaminophen toxicity.